Average Force Applied for Individual Tooth in All Ceramic Restoration - Halili, Rajmonda; Shabani, Alban; Asllani, Lumturie; Alidema, Sebahate Hamiti (European Journal of General Dentistry, 2024)
Objectives Occlusion plays an important role in the retention and stability of dental restorations. Aim of this study was to analyze occlusal loading detected on dental elements in patients with unilateral partial edentulism—class III Kennedy, before and immediately after prosthetic treatment with a zirconia-based bridge in maximal intercuspation position with the help of electronic system T-scan III.Materials and Methods The research sample consisted of a total of 60 patients who, based on the preset selection criteria, were divided into two groups: control group with 30 (100%) patients with intact dentition (Gr1) and study group with 30 (100%) patients with unilateral partial edentulism—class III Kennedy, analyzed before prosthetic treatment (Gr2) and immediately after prosthetic treatment with a zirconia-based bridge (Gr3).Results In Gr1, the highest average force applied for individual tooth had the tooth numbers: 17–14.6 ± 9.9%, 26–11.9 ± 6.8%, and 27–11.7 ± 6.8%. The lowest average value was registered for the teeth number 22–1.4 ± 1.3%, 12–1.9 ± 3.8%, and 13–2.9 ± 2.7%. In the group Gr2, the highest average force applied for individual tooth had the tooth numbers: 17–12.9 ± 35.6 and 21–9.6 ± 13.9%, whereas the lowest in teeth 24–2.7 ± 5.2 and 27–3.4 ± 6.8. In Gr3, the highest average force applied for individual tooth had the tooth numbers: 17–11.8 ± 15.4 and 14–9.8 ± 10.9%, whereas the lowest in the tooth 22–2.1 ± 2.6.Conclusion This study demonstrated that all patients with the loss of teeth showed occlusal discrepancies and functional disharmony. During the delivery of zirconia restorations in the future a careful analysis of occlusal contacts should be performed. T-scan III technology reduces the subjective interpretation of occlusal analysis data allowing records and measures the contacts between the teeth.
Keywords: occlusal force; occlusion; T-scan III